FREQUENCY OF ACUTE KIDNEY INJURY IN PATIENTS WITH ACUTE CORONARY SYNDROME UNDERGOING PERCUTANEOUS CORONARY INTERVENTION (The Research of Medical Science Review, 2025)
Objective: The objective of this study was to determine the frequency of acute kidney injury (AKI) in patients with acute coronary syndrome (ACS) undergoing percutaneous coronary intervention (PCI). Study Design: This cross-sectional study was designed to assess the prevalence of AKI in ACS patients undergoing PCI. Data were collected, including baseline demographic details, clinical history, and serum creatinine levels. Ethical approval was obtained, and informed consent was secured from all participants. Place and Duration of the Study: The study was conducted at the Department of Cardiology, Liaquat University of Medical and Health Sciences, Hyderabad/Jamshoro, from November 1, 2023, to April 30, 2024. Methodology: A total of 260 patients meeting the inclusion criteria were included in this study. Baseline demographic and clinical data were gathered, and serum creatinine levels were measured pre- and post-PCI to assess the development of AKI based on the KDIGO guidelines. A six-month study period was implemented following ethical approval, and the study methodology included both clinical assessments and laboratory tests to evaluate renal function in patients undergoing PCI. Results: The overall prevalence of AKI was found to be 15.4%. Stratified analysis revealed higher AKI rates in patients aged 41– 65 years (16.5%) compared to those aged 18–40 years (12.5%). AKI was also more prevalent in urban residents (20.6%) compared to rural residents (12.0%). Factors like hypertension (17.6% vs. 11.6%) and longer PCI duration (>1 hour, 17.0%) showed a non-significant trend towards higher AKI rates. Gender, diabetes, smoking, and family history did not significantly affect AKI outcomes. Conclusion: This study underscores the importance of monitoring renal function in ACS patients undergoing PCI. Findings highlight the need for early identification and management of at-risk patients to improve clinical outcomes and reduce AKI-related complications.